2007
DOI: 10.1063/1.2737386
|View full text |Cite
|
Sign up to set email alerts
|

Study and optimization of ion-irradiated high Tc Josephson junctions by Monte Carlo simulations

Abstract: Abstract.High Tc Josephson nanoJunctions (HTc JnJ) made by irradiation have remarkable properties for technological applications. However, the spread in their electrical characteristics increases with the ion dose. We present a simple model to explain the JnJ inhomogeneities, which accounts quantitatively for experimental data. The spread in the slit's width of the irradiation mask is the limiting factor. Monte Carlo simulations have been performed using different irradiation conditions to study their influenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
4
10
0
Order By: Relevance
“…Below T J a typical RSJ like behavior is observed 15 . Tc' and ΔTc', as well as Ic and ΔIc were found to follow well the evolution of T J and ΔT J , as already observed 14 . As t is increased, T J increases and the normal resistance Rn decreases (Figure 3 inset).…”
Section: Simulations and Experimental Detailssupporting
confidence: 65%
See 2 more Smart Citations
“…Below T J a typical RSJ like behavior is observed 15 . Tc' and ΔTc', as well as Ic and ΔIc were found to follow well the evolution of T J and ΔT J , as already observed 14 . As t is increased, T J increases and the normal resistance Rn decreases (Figure 3 inset).…”
Section: Simulations and Experimental Detailssupporting
confidence: 65%
“…where Tc is the critical temperature of a blank sample, namely 90 K. Experimentally, we have shown that for a given JJ, Tc' corresponds to the defect density in the centre of the barrier (dpa 0 ) 14 . In a JJ array there is an experimental scattering in Tc' (ΔTc'), corresponding to different dpa 0 values for each JJ with a distribution width σ dpa0 .…”
Section: Simulations and Experimental Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…• C increases the critical voltage I C R N [24,25,26,27]. The increase comes about from a much larger I C for a given temperature accompanied by a slight decrease in the voltage state resistance R N .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Good quality and highly reproducible 8-10 JJ can be built using YBa 2 Cu 3 O 7+␦ ͑YBCO͒, thanks to the optimization and control of the fabrication process. As the irradiation dose is increased, T J decreases and the spread in T J and I c increases as well, 12 reducing the reproducibility of the HT c JJ. High energy ions are used to locally disorder the superconductor through the slit and form the barrier.…”
mentioning
confidence: 99%